RESPONS FISIOLOGIS INDUK KAMBING PERANAKAN ETAWAH BUNTING TERHADAP SUPLEMENTASI TEPUNG DAUN KATUK (SAUROPUS ANDROGYNUS) DAN ZN BIKOMPLEKS - Yacob Robert Noach; Heroini Titi Handayani (Journal of Tropical Animal Science and Technology, 2019)
The experiment aimed to know the physiological response of Etawah Crossbred pregnant goat were fed katuk leave meal (Sauropus androgynus) and Zn biocomplex as supplement. Sixteen heads of Ettawa crossbred pregnant goat in early third months pregnancy were used in this experiment with 38 ± 2.3 kg of body weight. Completely random design with 4 treatments and 4 replications were applied in this experiment. Those treatment were, R0: farmer pattern fed (Leucaena + 0.5kg consentrate; R1: farmer pattern fed + 77.5g of katuk leave meal; R2: R1 + Zn biocomplex 1.03g/kg consentrate; dan R3: R1 + Zn biocomplex 2.06g/kg consentrate. Variable measured consist of the respiration rate, pulse rate and rectal temperature, using conventional method. Data were tabulated and analized by analysis of variance. Result showed that treatment have significant effect on respiration rate (P<.01) but no significant on pulse rate and rectal temperature of Ettawa crossbred pregnant goat. The average of respiration rate R0 to R3 were: 58.21;59.88; 61.80 and 63.31 breath/minute, respectively; average of pulse rate R0 to R3 were: 79.0; 79.85;81.1 dan 82.1 breath/minute; average of rectal temperature R0 to R3were: 38.3; 37.55; 38.27 and 38.36oC. It can be concluded that there was increase in repiration rate of Etawah Crossbred pregnant goat due to supplementation of katuk leave meal and Zn biocomplex.